Increasing the Interest of Students of SD Negeri 0514 Siali-Ali in Islamic Education Learning Through Project-Based Learning - El Amin, Mahmuddin Karim; Daulay, Halomoan; Nasution, Siti Hafsah (Jurnal Profesi Guru Indonesia, 2024)
This study aims to increase students' interest in Islamic religious education learning based on projects. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained using test and observation techniques. Tests are used to measure learning and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that Project-Based can increase students' interest in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 40.89%, the first cycle 68.87% and in the second cycle it increased to 90.32%. Thus, Project-Based can be used as an alternative to increase students' interest in Islamic religious education learning